SACRIFICE OF CONDOR (Vultur gryphus) IN LATE FORMATIVE OF CERRO PUNTA BLANCA, LURÍN VALLEY, PERU - Jave Calderón, Noé (2012)
In 2007 we found same partial skeletal of two Andean condors with evidence of cut marks and fractures postmortem in archaeological context of lime exploitation during the period Late Formative site of Cerro Punta Blanca (300-100 b.C.), it is located at lomas of Jatosisa, Lurin valley, Peru. These bones were associated to a head of snake of pottery. This association permitted us to relation to myth of transformation the snake to condor seen in petroglyphs, bone flutes and textiles of Archaic and Formative period and registered in etnohistorical dates and astronomic representations. This study confirms the importance of condor in Andean ritual context of inhabitants of green hills since two millenniums ago.